(3OQGSI GdLOhj hGOGQI GdeTQhYGJ GdUZjQIs - (3eMehO Gejf(B, (3Rhjds ((3GdGScfOQjI(B:s (3OGQ GdhaGA(B,s, 2001)
(3aj gPG GdcJGH jJfGhd eYfi GdOQGSI GdLOhi hCgejJgG hGdLhGfH GdGKfi YTQ dOQGSI GdLOhi ceG jYQV GdLGfH GdJShjbj dOQGSI GdLOhi hcGf GdeMJhi cGdJGdj (B: (3OQGSI GdLOhi eYfGgG hGgejJgG , LhGfH OQGSGJ GdLOhi , GdLGfH GdJShjbj dOQGSGJ GdLOhi , GdUfOhb GdGLJeGYj hHQGeL OYe YOI bWGYGJ, GOGQI GdeTQhYGJ GdUZjQI , eaghe GdGOGQI hhXjaJgG, JWhQ Yde haf GdGOGQI , GdJNWjW hGdGOGQI HGdCgOGa , GdJfXje hGdJTcjd , GdJhLjg , GdQbGHI hJbjje GdGfLGRGJ , GdJYGed eY eTGcd GdYed aj GdJWHjb GdYedj (B.s
(3HjHdjhZQGajG (B: (3U(B.197s
Keywords: (3EOGQI GdeTQhYGJs; (3OQGSI GdLOhis